2011
DOI: 10.1002/j.1532-2149.2011.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma corticosterone levels in mouse models of pain

Abstract: Our data indicate that HPA axis activation in acute and chronic pain models is time dependent and may be dissociated from evoked hyperalgesia. Therefore, HPA-axis activation represents an important variable to be considered when designing experimental assays of persistent pain as well as for interpretation of data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 77 publications
2
38
0
Order By: Relevance
“…The serum corticosterone concentration in OB-Sham group was significantly higher than that in NOB-Sham group ( p = 0.004) suggesting an increased activity of HPA axis induced by OB, which has been reported in previous studies (Marcilhac et al, 1999; Cryan and Mombereau, 2004). No difference was found in the serum corticosterone concentrations between NOB-SNL group and NOB-Sham group ( p = 0.516), which is consistent with previous observations (Ulrich-Lai et al, 2006; Alexander et al, 2009; Benedetti et al, 2012). Interestingly, corticosterone level in OB-SNL group was lower than that in OB-Sham group ( p < 0.001) and NOB-SNL group ( p = 0.048), indicating a decreased activity of HPA axis, which may due to the exhausted state of HPA axis in OB rats following SNL surgery.…”
Section: Resultssupporting
confidence: 92%
“…The serum corticosterone concentration in OB-Sham group was significantly higher than that in NOB-Sham group ( p = 0.004) suggesting an increased activity of HPA axis induced by OB, which has been reported in previous studies (Marcilhac et al, 1999; Cryan and Mombereau, 2004). No difference was found in the serum corticosterone concentrations between NOB-SNL group and NOB-Sham group ( p = 0.516), which is consistent with previous observations (Ulrich-Lai et al, 2006; Alexander et al, 2009; Benedetti et al, 2012). Interestingly, corticosterone level in OB-SNL group was lower than that in OB-Sham group ( p < 0.001) and NOB-SNL group ( p = 0.048), indicating a decreased activity of HPA axis, which may due to the exhausted state of HPA axis in OB rats following SNL surgery.…”
Section: Resultssupporting
confidence: 92%
“…However, it is noteworthy that corticosterone levels in the untested obese HFD mice were significantly elevated 18–20 hours after capsaicin treatment. Others have observed normalization of capsaicin-evoked corticosterone by 3 hours in C57BL/6J mice 1 , suggesting that obesity prolongs HPA axis activation evoked by capsaicin. Prolonged HPA axis activation in response to pain could have implications for pain modulation, especially in disorders of recurrent or chronic pain.…”
Section: Discussionmentioning
confidence: 95%
“…Some researchers reported higher levels of corticosterone in human patients with chronic back pain (Vachon-Presseau et al, 2013), while others not (Muhtz et al, 2013). In mice, persistent increase of corticosterone has been found in inflammatory pain models (Zheng et al, 2017), while an acute increase or no change of corticosterone was reported in neuropathic pain models (Yalcin et al, 2011; Benedetti et al, 2012). To minimize the effects of stress hormones on the results, we adopted neuropathic pain model in the present study.…”
Section: Discussionmentioning
confidence: 99%